MTBF of a Repairable Units with CCS Failures and M L Estimation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In this article, we discussed the method of maximum likelihood (M L) estimation to assess the estimates of mean time between failures (MTBF) of a redundant system. 2-unit identical system in case of series and parallel modes subject to individual, lethal and non-lethal common cause shock (LCCS & NCCS) failures is studied. System life times and repair times of the units are exponential. We developed the estimates of mean time between failures functions in case of series and parallel systems in the time off of analytical approach. We have presented the validity of the resulting estimates with the help of simulation.